Work-family conflict and job stress as predictors of quality of work-life among nurses (2024)
This study investigated predictors of quality of work life among nurses in Ipokia Local Government Area in Ogun State, Nigeria. A cross-sectional survey design was adopted to collect data using the Quality of Life Scale, Work-Family Conflict Scale, and Job Stress Scale. A purposive sampling technique was used to select 182 nurses (Females: 123; Males: 59). Data were analyzed using multiple regression analysis, t-test of independent mean, and one-way analysis of variance. Three hypotheses were generated and tested at a 0.001 level of significance. The result revealed that work-family conflict and job stress jointly predicted the quality of work-life among nurses [R2 = 286, F (2,181) = 37.648, p = .002). Also, job stress independently predicted the quality of work-life among nurses (β = .543, p = .001). However, work-family conflict did not independently predict the quality of work-life among nurses (β =-.001, p >.05). It was concluded that work-family conflict was a significant factor when combined with job stress but not an independent predictor of quality of work-life among nurses. Therefore, the Chief Medical Director and Human Resource Department of hospitals should monitor the stress levels of their nurses to ensure continuous productivity and avoid unnecessary breakdown of nurses at Work and home.